Determinants of Criminal Behavior in Society: A Socio-Legal and Criminological Analysis - Jamaluddin (Masterpiece, 2026)
Crime is a persistent social phenomenon closely linked to the dynamics of societal life. Its occurrence is influenced by a complex interplay of economic, social, cultural, psychological, and institutional factors. This study aims to examine the determinants of criminal behavior in society and to identify effective strategies for crime prevention. The research employs a normative juridical method with conceptual and sociological approaches, relying on primary, secondary, and tertiary legal sources collected through literature review. The findings reveal that economic hardship, including poverty and unemployment, serves as a primary driver of criminal activity. In addition, low levels of education contribute to limited legal awareness and reduced employment opportunities, thereby increasing the likelihood of deviant behavior. Social environmental factors, such as peer influence, weak social control, and unfavorable community conditions, further reinforce criminal tendencies. Family-related issues, including lack of supervision and dysfunctional relationships, also play a significant role. Moreover, psychological conditions, ineffective law enforcement, and rapid technological development—particularly in the digital sphere—have expanded opportunities for new forms of crime. This study concludes that crime is a multidimensional issue requiring comprehensive and integrated responses. Effective crime prevention should combine preventive, repressive, and rehabilitative measures, including improving socioeconomic welfare, strengthening education, enhancing law enforcement, and promoting responsible use of technology.